Major Role of Surrounding Environment in Shaping Biofilm Community Composition on Marine Plastic Debris - Basili, Marco; Quero, Grazia Marina; Giovannelli, Donato; Manini, Elena; Vignaroli, Carla; Avio, Carlo Giacomo; De Marco, Rocco; Luna, Gian Marco (Frontiers in Marine Science, 2020)
Plastic debris in aquatic environments is colonized by microbes, yet factors influencing biofilm development and composition on plastics remain poorly understood. Here, we explored the microbial assemblages associated with different types of plastic debris collected from two coastal sites in the Mediterranean Sea. All plastic samples were heavily colonized by prokaryotes, with abundances up to 1.9×107 cells/cm2. Microbial assemblages on plastics significantly differed between the two geographic areas but not between polymer types, suggesting a major role of the environment as source for the plastisphere composition. Nevertheless, plastic communities differed from those in the surrounding seawater and sediments, indicating a further selection of microbial taxa on the plastic substrates. The presence of potential pathogens on the plastic surface reflected the levels of microbial pollution in the surrounding environment, regardless of the polymer type, and confirmed the role of plastics as carriers for potentially pathogenic microorganisms across the coastal ocean, deserving further investigations.